Being Arab, Palestinian, Israeli, and Jew? Sayed Kashua’s ‘Arab Labor’ and the Challenge to Coexist in Israel - Pizzinato, Andrea (I.S. MED. - Interdisciplinary Studies on the Mediterranean, 2024)
In 2007, the first season of the sitcom ‘Arab Labor’ (in Hebrew: ‘Avodah ‘Aravit) was screened on primetime Israeli television. Most of the actors playing in the series are Palestinian, dialogues are mostly in Arabic, and the series is the first Israeli-Palestinian sitcom to bring the perspective of Palestinians in Israel to the general Israeli public. Its creator, Sayed Kashua, is a well-known Palestinian writer and journalist who was born and long lived in Israel, before moving to the United States. All of the above has represented a change in the place of Palestinian citizens within Israeli television, ensuring them renewed visibility among the Israeli-Jewish public. This contribution focuses on the first season of Arab Labor and conceptualizes it as a creative-subversive play that underscores the liminal condition of Palestinians in Israel, divided as they are between their social, cultural and national Arab-Palestinian heritage and their Israeli citizenship. By exploring some main characters, episodes, and cross-cut themes, it highlights the innovative power of Kashua’s representation of the entangled Arab-Palestinian identity in Israel. Through irony and sarcasm, Kashua lowers the tones of the political debate and stages stereotypical representations that Jews have of Arabs and vice versa, highlighting the inconsistency of these clichés and ridiculing them. The paper argues that Kashua’s creative resistance discourse (Goren 2014) on Arab-Palestinian citizens strives to spotlight the illusory character of exclusivist, supposedly pure imposed ethnonational identities, which ever fail to account for the complex entanglement of factors that contribute to shape hyphenated, fragmented identities, such as that of Palestinians in Israel. In order to present this argument, the article (1) sketches a historical background of Israel’s Palestinian history until the early 2000s and of Arab-Jewish relations in Israel; (2) it discusses relevant characters, episodes and cross-cut themes of the sitcom; (3) finally, it contextualizes Arab Labor into the wider artistic profile of Sayed Kashua.